Upaya Meningkatkan Hasil Belajar IPS Bagi Siswa Kelas VB SD GMIT Ende Melalui Metode Pembelajaran Kooperatif Tipe Jigsaw - Arlyn Martha Aurelia (Ekspektasi: Jurnal Pendidikan Ekonomi, 2022)
The research is aimed to improve: 1) students’ activities in learning social studies, and 2) students’ achievement in social studies for fifth grade students in SD GMIT Ende 4Kecamatan Ende Utara Kabupaten Ende of 2nd semester academic year 2018/2019through the application of cooperative learning type Jigsaw learning model. The research was done in Class V of SD GMIT Ende 4 Kecamatan Ende Utara Kabupaten Ende at 2nd semester of academic year 2018/2019. The research was taken place in three months, started on February up to April 2012. The subject of the research were Class V students at SD GMIT Ende 4 Kecamatan Ende Utara Kabupaten Ende of 2nd semester acedemic year 2018/2019 consisted of 26 students. The research concludes that the application of cooperative learning type Jigsaw learning model can: 1) improve students’ activities in learning social studies, and 2) students’ achievement in social studies for fifth grade students in SD GMIT Ende 4Kecamatan Ende Utara Kabupaten Endeof 2nd semester academic year 2018/2019.